Cecco Angiolieri : a study - Orwen, Gifford P. (Gifford Phillips), 1910-1997 (North Carolina studies in the Romance languages and literatures, 1979)
Volume215 in the North Carolina Studies in the Romance Languages and Literatures series.This volume is a thorough study of Cecco Angiolieri's life and work. Angiolieri was a thirteenth century Italian poet from Siena. Contents include a prefatory note on English translations of Angiolieri's work and general assessments of his work by Italian critics, a chapter placing the poet's life in context of thirteenth and fourteenth century Siena, a chapter treating the dominant topics of his poetry, and a final chapter on style and technique.